Structural and Mechanical Properties of Silica Mesoporous Films Synthesized Using Deep X-Rays: Implications in the Construction of Devices - Steinberg, Paula Y.; Lionello, Diego F.; Medone Acosta, Daiana E.; Zalduendo, M. Mercedes; Amenitsch, Heinz; Granja, Leticia P.; Marmiroli, Benedetta; Angelomé, Paula C.; Fuertes, M. Cecilia (Frontiers in Materials, 2021)
In recent years, the use of X-Rays (XR) irradiation for the production of ordered mesoporous thin films has been well established. This technique allows obtaining porous materials that contain thermal sensitive moieties or nanoparticles. Additionally, in combination with lithographic masks, the generation of high aspect ratio patterns of several geometrical shapes with micrometric resolution is possible. In this work, the structural and mechanical properties of porous silica thin films obtained by sol-gel method along with the exposure to high intensity XR is presented. Different templates, irradiation doses and post-synthesis treatments were evaluated by a combination of characterization techniques, including grazing incidence small-angle XR scattering, electronic microscopies, XR reflectometry and nanoindentation. The results demonstrate that all the irradiated oxides presented a highly ordered mesoporous structure, independently of the XR dose and post thermal treatment. Their mechanical properties, on the other hand, clearly depend on the irradiation dose; high hardness values were measured on samples irradiated at low doses but higher doses are necessary to obtain films with indentation modulus values similar to the obtained for thermally treated coatings. The accessible porosity, essential for the application of these films in devices for micro- and nanofluidics, is also dependent on the dose and the thermal treatment performed afterwards. The same tendency is observed for the films contraction and rigidity. After this characterization, it was concluded that thermal treatments are needed after the consolidation with XR to increase the accessibility and structural integrity of these porous oxides. Finally, the production of composites with metallic (Au and Ag) nanoparticles was tested which envisioned their applications in sensing and catalysis. Moreover, diverse geometrical patterns of both pure and Ag nanoparticles doped silica mesostructured films were obtained, demonstrating the feasibility of the proposed approach. The results presented in this work are of great importance to understand the transport mechanisms that operate in these silica porous films, in order to integrate them in different devices for lab-on-a-chip applications.